Jalan Panjang Tasawuf: Dari Tasawuf Awal Hingga Neo-Sufisme - Nasrullah, Achmad Muzammil Alfan (Spiritualita, 2021)
Sufism is a view of the world centered on God Almighty, Allah Almighty. Sufism talks about the essence of God Almighty only and not sinking into those who are not Him. Sufism is a view of the nature of a reality which in philosophy is classified as the science of nature or commonly referred to as "Ontology". The essence is not just to study and understand more deeply what is behind it. The term Sufism is not in the Qur'an and Sunnah, but rather based on the formulations and teachings of the teachers that do not contradict the main source of Islamic law, namely the Qur'an. The growth and development of Sufism has 4 periods, namely: early Sufism, Orthodox Sufism, Teousufi, and Neo-Sufism. In the archipelago, in the 17th century the development of Sufism itself was driven by Hamzah Fansuri and Syamsuddin Sumatrani in Sumatra and Nurudin ar-Raniri and Abdul Rauf al-Sinkili in Aceh. Sufism is classified into 2 types, namely Tasawuf Falsafi and Tasawuf Akhlaki. Sufism Falsafi, which was driven by Ibn Araby, is rich in ideas of understanding God, while Sufism Akhlaki emphasizes more on the charity of worship and akhlakul karimah in drawing closer to God. In Indonesia itself, Tasawuf Akhlaki is experiencing more rapid development. This can be proven through the large number of people who follow this teaching.